Can dynamic contrast-enhanced MRI contribute to improved assessment of rectosigmoid involvement in deep infiltrating endometriosis? - Hausmann, Daniel; Pérignon, Vasiliki; Grabherr Fawzi, Regula; Weiland, Elisabeth; Nickel, Marcel Dominik; Murer, Maurus; Bosshard, Lars; Prummer, Michael; Kubik-Huch, Rahel A. (In vivo, 2021)
Background/Aim: To determine whether a prototypical compressed-sensing volume-interpolated breath-hold (csVIBE) provides diagnostic value in detecting rectosigmoid infiltration in deep infiltrating endometriosis (DIE). Patients and Methods: csVIBE was employed in 151 women undergoing pelvic magnetic resonance imaging, of whom 43 had undergone surgery for suspected endometriosis. The accuracy of T2-weighted BLADE and BLADE/csVIBE, additional diagnostic value of csVIBE, and diagnostic confidence were rated by two readers. Additionally, the presence of the “mushroom cap sign” was assessed on BLADE and csVIBE. Results: The diagnostic accuracy, sensitivity, and specificity of BLADE and BLADE/csVIBE were not significantly different between Readers A and B. For both readers, the confidence in the diagnosis increased with csVIBE, but this increase in the odds ratio was not significant for both readers. Both readers preferred csVIBE over BLADE with regard to detection of the “mushroom cap sign.” Conclusion: csVIBE may provide a diagnostic benefit for surgical strategy selection through better delineation of the “mushroom cap sign.”
Gesehen am 19.10.2022